Inhalation of water electrolysis-derived hydrogen ameliorates cerebral ischemia–reperfusion injury in rats – A possible new hydrogen resource for clinical use. (29th October 2016) - Cui, Jin; Chen, Xiao; Zhai, Xiao; Shi, Dongchen; Zhang, Rongjia; Zhi, Xin; Li, Xiaoqun; Gu, Zhengrong; Cao, Liehu; Weng, Weizong; Zhang, Jun; Wang, Liping; et al.
Highlights: Water electrolysis-derived hydrogen is effective in cerebral I/R injury. Water electrolysis-derived hydrogen prevents oxidative stress and inflammation. Water electrolysis-derived hydrogen is safe for inhalation. Water electrolysis-derived hydrogen is a new hydrogen resource for clinical use. Abstract: Hydrogen is a kind of noble gas with the character to selectively neutralize reactive oxygen species. Former researches proved that low-concentration of hydrogen can be used to ameliorating cerebral ischemia/reperfusion injury. Hydrogen electrolyzed from water has a hydrogen concentration of 66.7%, which is much higher than that used in previous studies. And water electrolysis is a potential new hydrogen resource for regular clinical use. This study was designed and carried out for the determination of safety and neuroprotective effects of water electrolysis-derived hydrogen. Sprague–Dawley rats were used as experimental animals, and middle cerebral artery occlusion was used to make cerebral ischemia/reperfusion model. Pathologically, tissues from rats in hydrogen inhalation group showed no significant difference compared with the control group in HE staining pictures. The blood biochemical findings matched the HE staining result. TTC, Nissl, and TUNEL staining showed the significant improvement of infarction volume, neuron morphology, and neuron apoptosis in rat with hydrogen treatment. Biochemically, hydrogen inhalation decreased brain caspase-3, 3-nitrotyrosine and 8-hydroxy-2-deoxyguanosine-positive cells and inflammation factors concentration. Water electrolysis-derived hydrogen inhalation had neuroprotective effects on cerebral ischemia/reperfusion injury in rats with the effect of suppressing oxidative stress and inflammation, and it is a possible new hydrogen resource to electrolyze water at the bedside clinically.